Revealing Coprophilous Basidiomycetes in Sri Lanka: An Integrative Taxonomic Assessment of Dung‐Inhabiting Mushrooms - Nethmi M. Perera; Thivanka M. Peiris; Helani H. Munasinghe; Mayuri Munasinghe; Isuru Sakbo Uyangoda; Milan C. Samarakoon; Danushka S. Tennakoon; Buddhika P. Dharmasena; Samantha C. Karunarathna; Kasun M. Thambugala (New Zealand Journal of Botany, 2026)
Coprophilous fungi inhabit animal dung and play a crucial role in ecological balance by decomposing animal waste and serving as a food source for coprophagous and mycophagous arthropods. This study aimed to systematically characterize the diversity of coprophilous basidiomycetes across selected regions of Sri Lanka, and it characterized seven coprophilous basidiomycete specimens representing five distinct species from selected sites in Sri Lanka using both morphological and molecular methods. Specimens associated with elephant dung and horse manure were obtained from the Colombo, Gampaha, Nuwara Eliya, and Ratnapura districts. Taxonomical identification was achieved via integrated macro‐ and micromorphological analyses. Morphological characterization relied on detailed macro and micromorphological observations, while phylogenetic relationships were inferred from combined ITS and nLSU sequence data analyzed using maximum likelihood and Bayesian methods. Five species were identified and described at the species level, representing the first documented records of these taxa in Sri Lanka. These species include Conocybe volvata , Coprinopsis cinerea , Narcissea cordispora , Panaeolus antillarum , and Panaeolus cyanescens . The findings enhance the documentation of coprophilous fungal diversity in Sri Lanka and establish a foundation for future ecological and biotechnological research on dung‐inhabiting fungi in tropical ecosystems.

A multi-taxon evaluation of tropical–subtropical boundary using tree-of-life eDNA across Taiwanese waters - M. Aravinda Kishan Peiris; Shang-Yin Vanson Liu (Marine Environmental Research, 2026)

First Report of Agrocybe retigera and Scleroderma albidum from Sri Lanka based on Morphological and Molecular Identification - P. M. M. Peiris; Niranjan W. Gunasekara; Aseni N. Ediriweera; Pamoda B. Rathnaweera; Samantha C. Karunarathna; Muditha K. Meegahakumbura (New Zealand Journal of Botany, 2026)
The diversity of macrofungi in Sri Lanka remains largely unexplored, with many species yet to be documented. This study provides the first report of Agrocybe retigera and Scleroderma albidum from the Badulla District, Sri Lanka, based on morphological and molecular data. Macrofungal specimens were collected from different localities within the mid‐country intermediate zone and the up‐country intermediate zone in the Badulla District. Morphological characterization was conducted based on macroscopic and microscopic features. Molecular characterization was performed after extracting genomic DNA and amplifying the fungal internal transcribed spacer region using Polymerase Chain Reaction (PCR). Phylogenetic analysis was performed using the maximum likelihood method, which confirmed that the two fresh isolates clustered within the well‐supported A. retigera clade. In contrast, another isolate clustered within the S. albidum clade. Notably, to the best of our knowledge, this is the first molecular confirmation of A. retigera and S. albidum from Sri Lanka. Descriptions, illustrations, and phylogenetic analysis results of the two species are presented in this article.

Water quality and floating microplastics pollution along Southern to Northwestern Coast, Sri Lanka - M. G. Y. L. Mahagamage; P. Gajanayake; S. G. Gamage; D. Samarathunga; B. A. D. Peiris; M. M. K. I. Marasinghe; A. D. Igalavithana; H. D. L. Abeynayaka; A. Abeynayaka (Sri Lanka Journal of Aquatic Sciences, 2025)
Microplastics (MPs) are prevalent and dispersed in coastal ecosystems, heightening the risk of MPs consumption by marine wildlife, thereby leading to contamination of food webs. The present study investigated the abundance of MPs and respective water quality in coastal waters from Matara to Chilaw. MPs and water quality (pH, dissolved oxygen, electrical conductivity, turbidity, alkalinity, total dissolved solids, total suspended solids, total solids, and phosphates) were analysed in 12 sites in the study area in December 2021. MP analysis was done following the NOAA method and water quality was analysed according to the APHA standards. A total of 225 MP particles were found in all 12 sites covering Matara to Chilaw. The highest number of MP types was observed in the samples collected from Mattakkuliya (400 particles/m3). There were morphological differences among MPs and the highest to lowest morphological types were filament>film>fragment>pellets>foam, and the most dominant colour was blue. Based on FTIR analysis, polyethylene was identified as the most frequently detected (52%) polymer type of MPs in the analysed samples. Pearson correlation analysis indicated that there were no significant correlations among the water quality measures and MPs. However, further research is essential to determine the potential impacts of MPs on biotic and abiotic factors of the study locations.

Chnoospora minima: a Robust Candidate for Hyperglycemia Management, Unveiling Potent Inhibitory Compounds and Their Therapeutic Potential - Thilina Lakmini Gunathilaka; Upeka Bandaranayake; Mohamad Boudjelal; Rizwan Ali; Rajitha M. Silva; Kalpa W. Samarakoon; Pathmasiri Ranasinghe; L. Dinithi C. Peiris (Marine Biotechnology, 2024)

eDNA metabarcoding captures a decline of coral diversity at Taiping Island after an outbreak of Crown-of-Thorns starfish - M. Aravinda Kishan Peiris; Shang-Yin Vanson Liu; Joseph D. DiBattista; Michael Bunce; Yi-Hsuan Chen; Kang-Ning Shen; Chih-Wei Chang (Coral Reefs, 2024)

Tracking diarrhea viruses and mpox virus using the wastewater surveillance network in Hong Kong - Xiawan Zheng; Keyue Zhao; Bingjie Xue; Yu Deng; Xiaoqing Xu; Weifu Yan; Chao Rong; Kathy Leung; Joseph T. Wu; Gabriel M. Leung; Malik Peiris; Leo L.M. Poon; et al. (Water Research, 2024)

Development and application of influenza virus wastewater surveillance in Hong Kong - Xiawan Zheng; Keyue Zhao; Xiaoqing Xu; Yu Deng; Kathy Leung; Joseph T. Wu; Gabriel M. Leung; Malik Peiris; Leo L.M. Poon; Tong Zhang (Water Research, 2023)

Plant nanobionics: Fortifying food security via engineered plant productivity - Meththika Vithanage; Xiaokai Zhang; Viraj Gunarathne; Yi Zhu; Lasantha Herath; Kanchana Peiris; Zakaria M. Solaiman; Nanthi Bolan; Kadambot H.M. Siddique (Environmental Research, 2023)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Avian influenza A H7N9 virus infects human astrocytes and neuronal cells and induces inflammatory immune responses - Y. P. Ng; T. F. Yip; J. S. Malik Peiris; Nancy Y. Ip; Suki M. Y. Lee (Journal of NeuroVirology, 2018)

Comparison of Antimicrobial Properties of Silver Nanoparticles Synthesized from Selected Bacteria - M. M. K. Peiris; S. S. N. Fernando; P. M. Jayaweera; N. D. H. Arachchi; T. D. C. P. Guansekara (Indian Journal of Microbiology, 2018)

Erratum to: Nanobubble Ultrasound Contrast Agents for Enhanced Delivery of Thermal Sensitizer to Tumors Undergoing Radiofrequency Ablation - Reshani H. Perera; Luis Solorio; Hanping Wu; Mihika Gangolli; Eric Silverman; Christopher Hernandez; Pubudu M. Peiris; Ann-Marie Broome; Agata A. Exner (Pharmaceutical Research, 2014)

Nanobubble Ultrasound Contrast Agents for Enhanced Delivery of Thermal Sensitizer to Tumors Undergoing Radiofrequency Ablation - Reshani H. Perera; Luis Solorio; Hanping Wu; Mihika Gangolli; Eric Silverman; Christopher Hernandez; Pubudu M. Peiris; Ann-Marie Broome; Agata A. Exner (Pharmaceutical Research, 2014)

On-Command Drug Release from Nanochains Inhibits Growth of Breast Tumors - Pubudu M. Peiris; Morgan Tam; Peter Vicente; Aaron Abramowski; Randall Toy; Lisa Bauer; Aaron Mayer; Jenna Pansky; Elizabeth Doolittle; Samantha Tucci; Erik Schmidt; Christopher Shoup; et al. (Pharmaceutical Research, 2014)

Healthcare costs of methicillin resistant Staphylococcus aureus and Pseudomonas aeruginosa infections in veterans: role of vitamin D deficiency - D. Youssef; B. Bailey; A. El-Abbassi; M. Vannoy; T. Manning; J. P. Moorman; A. N. Peiris (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Field observations from the Aquila, Italy earthquake of April 6, 2009 - T. Rossetto; N. Peiris; J. E. Alarcon; E. So; S. Sargeant; M. Free; V. Sword-Daniels; D. Del Re; C. Libberton; E. Verrucci; P. Sammonds; J. Faure Walker (Bulletin of Earthquake Engineering, 2011)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The Indian Ocean tsunami of December 26, 2004: observations in Sri Lanka and Thailand - T. Rossetto; N. Peiris; A. Pomonis; S. M. Wilkinson; D. Del Re; R. Koo; S. Gallocher (Natural Hazards, 2007)

Genetic diversity in seed populations of Echinacea purpurea controls the capacity for regeneration, route of morphogenesis and phytochemical composition - Susan J. Murch; Sriyani E. Peiris; Wendy L. Shi; S. M. A. Zobayed; Praveen K. Saxena (Plant Cell Reports, 2006)